Consensus guidelines for antifungal prophylaxis in haematological malignancy and haemopoietic stem cell transplantation, 2014. Issue 12 (December 2014) - Fleming, S.; Yannakou, C. K.; Haeusler, G. M.; Clark, J.; Grigg, A.; Heath, C. H.; Bajel, A.; van Hal, S. J.; Chen, S. C.; Milliken, S. T.; Morrissey, C. O.; Tam, C. S.; et al.
Abstract There is a strong argument for the use of antifungal prophylaxis in high‐risk patients given the significant mortality associated with invasive fungal disease, the late identification of these infections, and the availability of safe and well‐tolerated prophylactic medications. Clinical decisions about which patients should receive prophylaxis and choice of antifungal agent should be guided by risk stratification, knowledge of local fungal epidemiology, the efficacy and tolerability profile of available agents, and estimates such as number needed to treat and number needed to harm. There have been substantial changes in practice since the 2008 guidelines were published. These include the availability of new medications and/or formulations, and a focus on refining and simplifying patient risk stratification. Used in context, these guidelines aim to assist clinicians in providing optimal preventive care to this vulnerable patient demographic.